Effect of Sphagneticola Trilobata Extract on Histological Wistar Rat Kidney Induced by DMBA - Bima Juanda Surbakti; Vivi Mardina; Beni Al Fajar (International Journal of Engineering, Science and Information Technology, 2021)
One factor can trigger the growth and development of cancer cells is free radicals that are from carcinogenic compounds such as dimethylbenz (α) anthracene (DMBA). The use of plant extracts as a preventive or curative in cases of tumors/cancer has been reported, however there is no reports about the in vivo study  for Sphagneticola trilobata plant. S. trilobata is an herbal plant that has pharmacological activities, potential to be developed as anticancer agent. This study aims to examine the anticancer effect of the methanol extract of S. trilobata leaves using histology observation on Wistar rat (Rattus novergicus) kidney which was induced by 7,12 dimethylbenz [α] anthracene (DMBA). The study used a completely randomized design with female rats (15 rats) grouped into 5 treatment groups, namely (i) the normal treatment group (KN), (ii) the DMBA-only treatment group (negative control, K(-)), (iii) the first dose (200 mg / kg BW) treatment group (KI), (iv) the second dose (300 mg / kg BW) treatment group (KII), and (v) the third dose (400 mg / kg BW) treatment group (KIII). DMBA was given orally at a concentration of 18 mg / kg BW for 4 times then continued for the extract. The results showed that cell damages (degeneration, necrosis and inflammation) were found mostly in negative controls. The dosage of 200 mg / kg BW of S. trilobata extract was the optimum dose in this study which was able to inhibit histological damage of kidney organs exposed to carcinogens DMBA by decreasing the level of degeneration, necrosis and inflammation.